Telecommunications development and economic growth in Namibia - Mvula, Nelly (Graduate School of Business (GSB), 2023)
The telecommunications sector is one of the industries that provide an enabling environment for other sectors to increase efficiency and productivity. With the emergence of Covid-19, which forced the world to adopt a new way of doing things, the telecommunications sector ensured minimum disruption to productivity by enabling remote working, online trading, and providing the connectivity required for online learning. The telecommunications sector is one of the key sectors identified by the Namibian Government as critical to the global and the Namibian economy, and the expansion of which has been included in the government planning documents such as the Vision 2030, Harambee Prosperity Plans, and the National Broadband Policy. However, the country had a low penetration rate of 41% in 2020 and there are interventions required to improve access to telecommunication services. This study employed the Autoregressive Distributed Lags (ARDL) bound test techniques and the Granger causality test based on secondary data obtained from the World Data Indicators (WDI), covering the period between 1995 and 2020. The results found no evidence of a long-run relationship between the telecommunications variables and economic growth, and this is attributable to the fact that the industry is still at an infant stage. The results of the Vector Autoregression (VAR) also didn't find a significant relationship between telecommunication variables and economic growth, except for number of individuals using the internet. The Granger causality tests revealed that there is no evidence of Granger causality between telecommunications development and economic growth in Namibia. The government should direct efforts towards implementing policies aimed at encouraging investments in telecommunication infrastructure and by further looking at complementary factors, which include investments in research and development aimed at improving the low internet penetration rate.